Recovery of hepatitis C specific T‐cell responses after rituximab therapy in hepatitis C mixed cryoglobulinemic vasculitis. Issue 5 (4th January 2018) - Mathur, Poonam; Emmanuel, Benjamin; Sneller, Michael; Zhang, Xiaozhen; Poonia, Bhawna; Kottilil, Shyamasundaran
Abstract : Mixed cryoglobulinemic vasculitis is associated with monoclonal B cell expansion in patients with chronic hepatitis C (HCV) infection. B cell depletion therapy using rituximab, a CD20 monoclonal antibody, has been successful in achieving remission from symptomatic disease. This study investigated whether B cell depletion therapy has an impact on activation of HCV‐specific T cell phenotype and function. Nineteen patients with Hepatitis C mixed cryoglobulinemic vasculitis were treated with 4 cycles of rituximab (375 mg/m 2 ) and variables were measured 6 months after therapy. Using flow cytometry and Enzyme‐Linked Immunospot assay, the number of activated and tissue‐like B cells and number of T cells expressing Programmed cell death protein 1 (PD‐1), T‐cell immunoglobulin and mucin‐domain containing‐3 (TIM‐3), and multiple cytokines were measured before and after rituximab therapy. B cell depletion therapy is associated with a significant ( P < 0.0001) decline in peripheral T cells with exhaustive phenotype, from pre‐therapy to post‐therapy‐of rituximab (mean ± standard error): CD4+ (16.9 ± 0.9% to 8.9 ± 1.0%) and CD8+ (6.8 ± 0.6% to 3.0 ± 0.5%) T cells expressing PD‐1 and CD4+ (11.0 ± 1.0% to 6.1 ± 0.8%) and CD8+ (12.7 ± 0.7% to 6.4 ± 0.4%) T cells expressing TIM‐3. In addition, there was a significantly higher percentage of peripheral CD8+ T cells responding to HCV peptide stimulation in vitro secreting IFN‐γ (4.55 ± 0.3 to 9.6 ± 1.0 IFN‐γ /10 6 PBMCs, P < 0.0001), and more than one cytokine (1.3 ± 0.1% to 3.8 ± 0.2%, P < 0.0001) after therapy compared to pre‐therapy. B cell depletion therapy results in recovery of T cell exhaustion and function in patients with HCV cryoglobulinemic vasculitis.